Echo in the canyon [videorecording (DVD)] - Slater, Andrew (Filmmaker); Barrett, Eric; Dylan, Jakob, 1969- (Greenwich Entertainment, 2019)
Documentary celebrating the explosion of popular music that came out of LA's Laurel Canyon in the mid-'60s as folk went electric and the Byrds, the Beach Boys, Buffalo Springfield, and the Mamas and the Papas gave birth to the California Sound. Featuring Jakob Dylan, the film includes conversations and performances with Brian Wilson (the Beach Boys), Michelle Phillips (the Mamas & the Papas), Stephen Stills (Buffalo Springfield), David Crosby, Roger McGuinn (the Byrds), their contemporaries Ringo Starr, Eric Clapton, Graham Nash, and younger followers Jackson Browne and Tom Petty, as well as contemporary musicians influenced by their music.